Long-term treatment of severe hypertension with minoxidil. - Nawar, T. (1977)
Minoxidil, a new potent hypotensive agent, was used as the primary antihypertensive agent in 11 patients--10 men and 1 woman aged 35 to 54 years with severe hypertension that was refractory to treatment with maximal (or maximally tolerated) doses of conventional antihypertensive agents. Six patients had severely impaired renal function and three of them were undergoing long-term hemodialysis. The patients were given 2.5 to 40 mg/d of minoxidil for periods of 2 to 29 months. All except one who was almost anuric received propranolol and diuretics. Blood pressure was controlled satisfactorily in all patients. In two patients the hypertension became partially resistant after 1 year of treatment. The main side effects were sodium retention, tachycardia and hirsutism. Renal function remained stable or improved and hemodialysis was discontinued in two patients. Minoxidil is a remarkably potent hypotensive with relatively few side effects and seems particularly advantageous in patients with chronic renal failure.